Micro‐ribonucleic acid‐binding site variants of type 2 diabetes candidate loci predispose to gestational diabetes mellitus in Chinese Han women. Issue 5 (2nd March 2018) - Wang, Xiaojing; Li, Wei; Ma, Liangkun; Ping, Fan; Liu, Juntao; Wu, Xueyan; Mao, Jiangfeng; Wang, Xi; Nie, Min
Abstract: Aims/Introduction: Emerging evidence has suggested that the genetic background of gestational diabetes mellitus (GDM) was analogous to type 2 diabetes mellitus. In contrast to type 2 diabetes mellitus, the genetic studies for GDM were limited. Accordingly, the aim of the present study was to extensively explore the influence of micro‐ribonucleic acid‐binding single‐nucleotide polymorphisms (SNPs) in type 2 diabetes mellitus candidate loci on GDM susceptibility in Chinese. Materials and Methods: A total of 839 GDM patients and 900 controls were enrolled. Six micro‐ribonucleic acid‐binding SNPs were selected from 30 type 2 diabetes mellitus susceptibility loci and genotyped using TaqMan allelic discrimination assays. Results: The minor allele of three SNPs, PAX4 rs712699 (OR 1.366, 95% confidence interval 1.021–1.828, P  = 0.036), KCNB1 rs1051295 (OR 1.579, 95% confidence interval 1.172–2.128, P  = 0.003) and MFN2 rs1042842 (OR 1.398, 95% confidence interval 1.050–1.862, P  = 0.022) were identified to significantly confer higher a risk of GDM in the additive model. The association between rs1051295 and increased fasting plasma glucose ( b  = 0.006, P  = 0.008), 3‐h oral glucose tolerance test plasma glucose ( b  = 0.058, P  = 0.025) and homeostatic model assessment of insulin resistance ( b  = 0.065, P  = 0.017) was also shown. Rs1042842 was correlated with higher 3‐h oral glucose tolerance test plasma glucose ( b  = 0.056, P  = 0.028). However, no significant correlation between the other included SNPs ( LPIN1 rs1050800, VPS26A rs1802295 and NLRP3 rs10802502) and GDM susceptibility were observed. Conclusions: The present findings showed that micro‐ribonucleic acid‐binding SNPs in type 2 diabetes mellitus candidate loci were also associated with GDM susceptibility, which further highlighted the similar genetic basis underlying GDM and type 2 diabetes mellitus.